INOVASI DALAM PENGELOLAAN KEUANGAN, SARANA DAN PRASARANA PENDIDIKAN - Suci Hidayati; Hendi, Karoma, Mardiah Astuti (ADMIN: Jurnal Administrasi Negara, 2023)
Innovation in the management of education finances, facilities and infrastructure is an important step to increase the efficiency and effectiveness of the management of educational resources. The use of information technology in budget management and financial reporting is one of the innovations that enables more efficient, accurate and transparent financial management. In addition, innovation is also implemented in the management of educational facilities and infrastructure, using modern technology, better management and efficient use of energy. These innovations provide benefits such as reduced operational costs, increased learning quality, and increased educational accessibility. Good management of educational facilities and infrastructure is also important to ensure the sustainability and relevance of quality education. In this context, school principals have an important role in managing human resources, facilities and infrastructure to optimally achieve educational goals. Therefore, innovation in the management of education finances, facilities and infrastructure is an important step to improve the quality of education as a whole. In this study, a qualitative research approach was used to gain an in- depth understanding of innovation in the management of education finance, facilities and infrastructure. Innovation in financial management, educational facilities and infrastructure has an important role in improving the quality of education. This innovation includes the use of information and communication technology, infrastructure improvements, and improving the quality of learning programs.